Study on Illumination Intensity and Duration of LED Light Sources for a Weaned Piglet House without Natural Light - Yaqiong Zeng; Dingbiao Long; Bin Hu; Hao Wang; Shihua Pu; Yue Jian; Zuohua Liu; Shunlai Xu (Agriculture, 2023)
Lighting is an important environmental parameter in livestock farming, which can affect the physiology and behavior of animals, and it can regulate animal production. To explore the comprehensive effects of light intensity and duration on the performance, behavior, and physiological indicators of piglets, a 3 × 2 two-factor experiment (three levels of lighting intensity × two lighting durations) was conducted. The three light intensities used were high (100–120 lux), medium (40–50 lux), and low (5–20 lux). The two lighting durations were 8 h and 10 h of light per day. The experiment used a total of six lighting combinations, which corresponded with the six test units. A total of 96 Landrace–Yorkshire hybrid piglets, with an initial body weight of 13.23 ± 0.18 kg, were randomly assigned to six lit units, four pens per unit, and four piglets per pen. The results showed that lighting intensity and duration had no significant effect on the average daily feed intake, average daily gain, feed/gain, or water consumption of pigs (p > 0.05). For IgM, the main effect caused by the light duration was significant. When the light intensity was 5–20 lux and 40–50 lux, the serum IgM levels of piglets in the 10 h/day light group were 45.80% and 39.54% higher than those in the 8 h/day group, respectively (p < 0.05). For SOD and GSH-Px, the interaction between the lighting duration and intensity was significant (p < 0.05). In the 8 h/day light group, the serum SOD levels of piglets at light intensities of 5–20 lux and 40–50 lux were significantly higher than those at 100–120 lux (p < 0.05). When the light intensity was 5–20 lux and 40–50 lux, the SOD level in the 8 h/day group was significantly higher than that of the 10 h/day group (p < 0.05). The main effect of lighting duration on lying down and abnormal behavior was significant (p < 0.05). In the 8 h/day light group, the abnormal behavior of piglets under a light intensity of 5–20 lux was twice that of 40–50 lux (p < 0.05), and the lying percentage of piglets under a light intensity of 40–50 lux was 14.03% higher than that of piglets under a light intensity of 5–20 lux (p < 0.05). Overall, under the conditions used in this study, although extending the duration of light with an intensity of 40–50 lux to 10 h can improve some immune-related indicators, the extent of this effect was limited. The recommended lighting scheme for piglet houses is a light intensity of 40–50 lux and a lighting duration of 8 h. However, the range of lighting conditions set in this study was still very limited, and various environmental factors must be comprehensively considered in an actual production setting.